Seed Germination under Simulated Water Stress as Drought Tolerance Test in Maize - J.S. BHAT; R.D. SINGH (Seed Research, 2026)
Six inbreds possessing various degrees of drought tolerance along with their 15 F₁s were used to study seed germination and early seedling growth under simulated drought using polyethylene glycol (PEG) and mannitol solution at 0.5 MPa (-5.0 bars). Germination percentage decreased greatly under osmotic stress. The results obtained in PEG and mannitol were parallel. However, tolerant parents and hybrids showed less decrease in germination percentage. Reduction in root and shoot length and increase in root-shoot ratio were some other effects of osmotic stress on early seedling growth. Osmotic stress caused greater decrease in shoot length. However, tolerant genotypes showed lower decrease in root length and increased root-shoot ratio. Almost similar trend was noticed in F₁, F₂ and backcrosses. This suggested the utility of laboratory screening by taking per cent decrease in germination and increased root-shoot ratio as criteria for preliminary screening of genotypes for drought tolerance. The germination percentage in osmotic stress showed positive correlation with root-shoot ratio and grain yield under rainfed and limited irrigation conditions.